Calculating equation of the curve.
y-6√(2) = a(x-6)² --- (1).
Substituting x = 0, y = 0 to get a.
It implies;
-6√(2) = 36a
a = -(1/(3√(2)) --- (2).
Substituting (2) in (1).
y-6√(2) = -(1/(3√(2))(x-6)²
y = -(1/(3√(2))(x²-12x+36)+6√(2)
y = -(x²/(3√(2))+2√(2)x-6√(2)+6√(2)
y = -(x²/(3√(2))+2√(2)x --- (3).
Where (3) is the equation of the curve.
Calculating x, when y is ⅓(10√(2)).
⅓(10√(2)) = -(x²/(3√(2))+2√(2)x
(x²/(3√(2))-2√(2)x+⅓(10√(2)) = 0
x²-12x+20 = 0
Resolving the quadratic equation.
(x-6)² = -20+(-6)²
(x-6)² = -20+36
x = 6±√(16)
x = 6±4
Therefore;
x ≠ 10
x = 2.
Calculating Area B.
It is;
(Area under the curve at x = 0 and x = 2)-Area triangle with height and base ⅓(10√(2)) units and 2 units respectively.
= ⅑(32√(2))-0.5(2*⅓(10√(2)))
= ⅑(32√(2))-⅓(10√(2))
= ⅑(32√(2)-30√(2))
= ⅑(2√(2)) square units.
Calculating Area C.
It is;
(Area under the curve at x = 2 and x = 6)-Area triangle with height and base ⅓(10√(2)) units and 2 units respectively-Area triangle with height and base 6√(2) units and 2 units respectively.
= ⅑(184√(2))-0.5(2*⅓(10√(2))-0.5(2*6√(6))
= ⅑(184√(2))-⅓(10√(2))-6√(2)
= ⅑(184√(2)-30√(2)-54√(2))
= ⅑(184√(2)-84√(2))
= ⅑(100√(2)) square units.
Therefore;
Area B÷Area C Exactly is;
⅑(2√(2))÷⅑(100√(2))
= 1/50
We appreciate you contacting us. Our support will get back in touch with you soon!
Have a great day!
Please note that your query will be processed only if we find it relevant. Rest all requests will be ignored. If you need help with the website, please login to your dashboard and connect to support